Penerapan Pemuridan di JKI Jakarta Praise Community Church (JPCC) Dalam Masa Pandemi - Sen, Thio Yan; Tanudjaja, Daniel Januar; Edwin, Edwin (STT Kingdom, 2024)
This study aims to describe the congregation's understanding of discipleship and its application at JKI Jakarta Praise Community Church (JPCC) during a pandemic. The informants in this study were Date Facilitators, Date Leaders and Daters. Data collection techniques used are interviews and observation. Data collected was analyzed by stages (1) Condensation (2) Data Display (3) Drawing Conclusion. The results of the study show that (1) the congregation has understood the meaning of discipleship; and (2) the implementation of discipleship at JKI Jakarta Praise Community Church (JPCC) is going good enough. Based on the results of this research, several suggestions were proposed including: (1) JKI Jakarta Praise Community Church (JPCC) still needs to hold seminars or training regarding discipleship; (2) JKI Jakarta Praise Community Church (JPCC) need to continue to provide encouragement and enthusiasm to all parties involved in discipling; and (3) The discipleship department or division at JKI Jakarta Praise Community Church (JPCC) creates a special book module or guide on how to be more creative and innovative in carrying out online discipleship